PENGARUH METODE PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUALISATION, INTELLECTUALLY) TERHADAP HASIL BELAJAR IPA TERPADU KELAS VIII MTS RIYADLATUL ULUM - Della Susiani; Triana Asih; HRA Mulyani (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
This study aims to determine the effect of the SAVI learning method (Somatic, Auditory, Visualization, Intellectually) on the integrated science learning outocomes of eighth grade students of MTs Riyadlatul 'Ulum. This type of research is quantitative with a quasi-experimental form. The place of research is at MTs Riyadlatul 'Ulum. The population in this study were students of class VIII Mts Riyadlatul 'Ulum. The samples used were class VIII B and class VIII C. Class VIII B became the experimental class and class VIII C became the control class. The prerequisite test in this study used normality test, homogeneity test, and hypothesis testing. Hypothesis test is t-test. The result of testing the t-test formula is that the t-score value is greater than the t-table (3,249>2,015). This shows that there is an effect of the SAVI Learning Method (Somatic, Auditory, Visualization, Intellectual) on the integrated science learning outcomes of class VIII MTs Riyadlatul 'Ulum. The effect of the SAVI method makes the results significant. The SAVI (Somatic, Auditory, Visualization, Intellectually) method is learning that uses physical movement with intellectual activity and the use of all the senses that have a big influence on learning. Learning using the SAVI method can motivate students to study hard so as to improve student learning outcomes. The SAVI method has the advantage of increasing students' intelligence in a fully integrated manner through physical integration with intellectual activities.